Monitoring impact damaging of thermoplastic composites. (November 2015) - Boccardi, S; Carlomagno, G M; Meola, C; Russo, P; Simeoli, G
Abstract: Thermoplastic composites are becoming ever more attractive also to the aeronautical sector. The main advantage lies in the possibility to modify the interface strength of polypropylene based laminates by adjusting the composition of the matrix. Understanding these aspects is of great importance to establish a possible link between the material toughness and the matrix ingredients. The aim of the present work is to ascertain the ability of an infrared imaging device to visualize any change, in the material behaviour to low energy impact, induced by changes in the matrix composition. Attention is given to image processing algorithms; in particular, an original procedure to measure the extension of the impact-affected area is proposed.